2011
DOI: 10.1007/978-3-642-18418-5_6
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainties and Systematics in Stellar Evolution Models of Red Giant Stars

Abstract: In this last decade, our knowledge of evolutionary and structural properties of stars of different mass and chemical composition has significantly improved. This notwithstanding, updated stellar models are still affected by significant and, usually, not negligible uncertainties. These uncertainties are related to our poor knowledge of some physical processes occurring in the real stars such as the efficiency of mixing processes. These drawbacks of stellar models have to be properly taken into account when comp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 82 publications
(152 reference statements)
0
5
0
Order By: Relevance
“…Meissner & Weiss [18] showed that (for their models) the bump location of GC-type isochrones was inconsistent with the TO brightness for any given age. The fact that the bump tends to be too bright by about 0.2 mag was confirmed, among others, by [13], in particular for the lowest metallicities.…”
Section: The Location Of the Bumpmentioning
confidence: 60%
See 1 more Smart Citation
“…Meissner & Weiss [18] showed that (for their models) the bump location of GC-type isochrones was inconsistent with the TO brightness for any given age. The fact that the bump tends to be too bright by about 0.2 mag was confirmed, among others, by [13], in particular for the lowest metallicities.…”
Section: The Location Of the Bumpmentioning
confidence: 60%
“…On the other hand, "several times the typical value" for overshooting from the bottom of the convective envelope is needed for an efficient 13 C neutron source [27], and generally, in 3d-hydro simulations a variation by a factor of 10 is found [28].…”
Section: The Asymptotic Giant Branch Phasementioning
confidence: 99%
“…However, the significant improvements of the last decade regarding stellar physics inputs (see Cassisi 2005Cassisi , 2009Cassisi , 2010Cassisi , 2012, and references therein) require an updated theoretical framework for these populations. A&A 558, A46 (2013) At the other extreme of the metallicity spectrum, both spectroscopic and photometric surveys (see Gonzalez et al 2011, and references therein) show that the Galactic bulge metallicity distribution (peaked at about solar metallicity) displays an extended tail reaching [Fe/H] ∼ +1.0.…”
Section: Introductionmentioning
confidence: 99%
“…Even more important, however, is the fact that we have used the position of the RGB bump as a reference point in our analysis. Unfortunately, the predicted RGB bump position is known to be affected by ill-constrained physical processes, and is thus subject to large systematic errors (e.g., [3], and references therein). Such errors were not taken into account in the present study.…”
Section: −12mentioning
confidence: 99%
“…This way, we obtain evolutionary tracks for 02004-p. 3 Based on the computed tracks, we then evaluate the theoretically expected TRGB and RGB bump I -band magnitudes, and finally derive the predicted dependence of I TRGB Bump on ν . This is shown as filled circles in Figure 5.…”
Section: Theoretical Frameworkmentioning
confidence: 99%